Changes in health in Belgium, 1990-2016: a benchmarking analysis based on the global burden of disease 2016 study - C. Maertens de Noordhout; H. Van Oyen; N. Speybroeck; B. Devleesschauwer (BMC, 2018)
Abstract Background Despite increasing of the Belgian health expenditures, several indicators related to population health showed poor results. The objectives of this study were to perform an in-depth analysis of the secular trend of Belgian health status using the Global Burden of Disease (GBD) 2016 study results for Belgium, and to compare these results with other European countries. Methods We collected results of the Global Burden of Disease 2016 study through the GBD results and visualization tools. We benchmarked Belgian GBD results with the other initial members of the European Union (EU15). Results Belgium performed significantly better in 2016 than in 1990 in terms of age-standardized (AS) Year of Life Lost (YLL) rates but not significantly different in terms of AS Year Lived with Disability (YLD) and Disability-Adjusted Life Year (DALY) rates. The contribution of AS YLDs to total of AS DALYs increased from 1990 (42%) to 2016 (54%). Although AS YLD and DALY rates did not seem to differ between Belgium and the EU15 from 1990 to 2016, the ranking of Belgium among the EU15 in terms of AS DALY and YLL rates was worse in 2016 than in 1990. Belgium had significantly higher AS YLL rates for lower respiratory infections (B: 264 AS YLLs [95% uncertainty interval [UI] 231-301] per 100,000; EU15: 188 AS YLLs [95%UI 168-212] per 100,000), chronic obstructive pulmonary disease (B: 368 AS YLLs [95%UI 331-407] per 100,000; EU15: 285 AS YLLs [95%UI 258-316] per 100,000) and tracheal, bronchus, and lung cancer (B: 785 AS YLLs [95%UI 699-879] per 100,000; EU15: 613 AS YLLs [95%UI 556-674] per 100,000). Conclusion Belgium's ranking among the EU15 in terms of AS YLL and DALY rates decreased from 1990 to 2016. Significant health gains appear possible by acting on risk factors directly linked to a significant part of the Belgian burden of diseases, i.e., alcohol and tobacco consumption, and high body mass index. National burden of disease estimates can help defining Belgian health targets and are necessary as external validity of GBD results is not always guaranteed.